Brevican, Neurocan, Tenascin-C, and Tenascin-R Act as Important Regulators of the Interplay Between Perineuronal Nets, Synaptic Integrity, Inhibitory Interneurons, and Otx2 - Mueller-Buehl, Cornelius; Reinhard, Jacqueline; Roll, Lars; Bader, Verian; Winklhofer, Konstanze F.; Faissner, Andreas (Frontiers in Cell and Developmental Biology, 2022)
Fast-spiking parvalbumin interneurons are critical for the function of mature cortical inhibitory circuits. Most of these neurons are enwrapped by a specialized extracellular matrix structure (ECM) called perineuronal net (PNN), which can regulate their synaptic input. In this study, we investigated the relationship between PNNs, parvalbumin interneurons and synaptic distribution on these cells in the adult primary visual cortex (V1) of quadruple knockout mice deficient for the ECM molecules brevican, neurocan, tenascin-C and tenascin-R. We used super-resolution structured illumination microscopy (SIM) to analyze PNN structure and associated synapses. Additionally, we examined parvalbumin and calretinin interneuron populations. We observed a reduction in the number of PNN-enwrapped cells and a clear disorganization of the PNN structure in the quadruple knockout V1. This was accompanied by an imbalance of inhibitory and excitatory synapses with a reduction of inhibitory and an increase of excitatory synaptic elements along the PNNs. Also, the number of parvalbumin interneurons was reduced in the quadruple knockout, while calretinin interneurons, which do not wear PNNs did not display differences in number. Interestingly, we found the transcription factor Otx2 homeoprotein positive cell population also reduced. Otx2 is crucial for parvalbumin and PNN maturation and a positive feedback loop between these parameters has been described. Collectively, these data indicate an important role of brevican, neurocan, tenascin-C and tenascin-R in regulating the interplay between PNNs, inhibitory interneurons, synaptic distribution as well as Otx2 in the V1.